De pontibus a pocket-book for bridge engineers - Waddell, J. A. L. (John Alexander Low), 1854-1938 (Chapman & Hall, 1898)
This manual on bridge engineering does not cover suspension bridges, as the long spans involved need specifications working out case by case.